The Linearization of Affixes: Evidence from Nuu-chah-nulth - Wojdak, Rachel (Studies in Natural Language and Linguistic Theory, 2008)
The linearization of syntactic constructs stands at the forefront of current research on the syntax-phonology interface. This book examines the problem of linearization from a new perspective: that of the linearization of affixes. The driving proposal of this book is that affixation provides a means of satisfying the universal requirement that linguistic outputs be linearized. This hypothesis is tested against extensive original data from Nuu-chah-nulth ("Nootka"; Wakashan family), an endangered Amerindian language remarkable for its complex morphology. This volume introduces typologically rare affixation effects to current theoretical debates surrounding the division of labour between the modules of the grammar.